E. S. Piccolomini Historia de duobus amantibusa: Nyelvi és kulturális gátak tizenhat korai fordítás tükrében - Máté, Ágnes (Antikvitás & Reneszánsz, 2019)
The paper discusses general factors influencing the translators of Eneas Silvius Piccolomini’s Historia de duobus amantibus, who translated the love story from Latin into eight vernacular languages during the 15-16th centuries. These factors fell into two broader categories: linguistic limitations and cultural-moral restrictions. The paper argues that the limited knowledge of Latin language and the deficiencies of knowledge concerning classical culture or the moral reservations towards the original Latin text from the part of the translators all influenced the love story’s translations. The paper offers a series of case studies to illustrate how translators operational in different vernaculars had faced similar problems and how diverse their responds were to them in altogether sixteen early translations of Historia. Originally written as a conference presentation in 2017, the present paper gives a short summary of the conclusions connected to translatology of the author’s recently published monograph: MÁTÉ (2018).